Modelado dinámico de un vehículo autónomo articulado todoterreno - Puignau, Francisco (2018)
Faculty of Engineering in collaboration with the National Agricultural and Livestock Investigation Institute is developing a low cost platform capable of dealing with challenges imposed by agricultural activities, specifically, fruit transportation inside fields. In this context, the consequent dissertation focuses on the development of a dynamic model of an all terrain articulated autonomous vehicle to be applied in the aforementioned platform. The study includes the kinematic and dynamic analysis of the vehicle. Once those models are deducted, they are put together against the ones obtained for a biarticulated robot arm without ground fixation. To sum up, results will be adapted for computational simulation which was done via Gazebo, an ambience of the robot operating system ROS. Through this simulations it was possible to determine the model validity for the autonomous operating robotic platform.